2013
DOI: 10.1038/ng.2844
|View full text |Cite
|
Sign up to set email alerts
|

EIF2AK4 mutations cause pulmonary veno-occlusive disease, a recessive form of pulmonary hypertension

Abstract: Pulmonary veno-occlusive disease (PVOD) is a rare and devastating cause of pulmonary hypertension that is characterized histologically by widespread fibrous intimal proliferation of septal veins and preseptal venules and is frequently associated with pulmonary capillary dilatation and proliferation. PVOD is categorized into a separate pulmonary arterial hypertension-related group in the current classification of pulmonary hypertension. PVOD presents either sporadically or as familial cases with a seemingly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
330
2
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 373 publications
(360 citation statements)
references
References 35 publications
13
330
2
15
Order By: Relevance
“…Idiopathic PVOD is a rare disease characterised by a diffuse obstruction of the small pulmonary veins [27][28][29]. DORFMÜLLER et al [30] have shown that PVOD-like lesions are common in lung tissue in SSc-PH while, more recently, GÜNTHER et al [11] have shown that 61.5% of SSc-PH patients have HRCT signs suggestive of PVOD.…”
Section: Pulmonary Veno-occlusive Diseasementioning
confidence: 99%
“…Idiopathic PVOD is a rare disease characterised by a diffuse obstruction of the small pulmonary veins [27][28][29]. DORFMÜLLER et al [30] have shown that PVOD-like lesions are common in lung tissue in SSc-PH while, more recently, GÜNTHER et al [11] have shown that 61.5% of SSc-PH patients have HRCT signs suggestive of PVOD.…”
Section: Pulmonary Veno-occlusive Diseasementioning
confidence: 99%
“…Additional eIF2 kinases include PERK (PEK/EIF2AK3), induced by endoplasmic reticulum stress, PKR (EIF2AK2), activated by doublestranded RNA produced during viral infection, and HRI (EIF2AK1), which functions to couple protein synthesis in erythroid tissues to iron availability (1)(2)(3). Together these eIF2 kinases are essential for health, with loss of GCN2 in mice leading to increased morbidity during nutrient depletion (13), and in humans, EIF2AK4 (GCN2) mutations cause pulmonary veno-occlusive disease, a form of pulmonary hypertension (14). Disruptions of PERK trigger neonatal diabetes, and disruptions in bone, liver, and digestive systems in humans (Wolcott-Rallison syndrome) and in mouse models (15)(16)(17).…”
mentioning
confidence: 99%
“…Histological examination of the lungs from bi-allelic EIF2AK4 mutations carriers revealed extensive occlusion of pulmonary veins by fibrous tissue, intimal thickening of venules and small veins in the lobular septae and localised capillary proliferation. These histological features correspond to the clinical entities of PVOD/PCH, which are currently believed to be manifestations of the same rare underlying condition with an estimated prevalence of less than one case per million [39,41,43,45]. The EIF2AK4 gene is currently the only gene identified in heritable PVOD/PCH.…”
mentioning
confidence: 69%
“…In 2014, bi-allelic EIF2AK4 mutations (coding for eukaryotic translation initiation factor 2α kinase 4) were demonstrated to predispose to PVOD/PCH. Mutations in the EIF2AK4 gene are transmitted as an autosomal recessive trait with an unknown penetrance [41][42][43]. Distinguishing PVOD/PCH from PAH on clinical grounds can be challenging, since physical and haemodynamic findings are broadly similar.…”
mentioning
confidence: 99%